A development plan for the Barangay Salawag reading center in Dasmariñas, Cavite - Espiritu, Rhodora D. (2018)
Barangay Salawag is one of the 75 barangays in Dasmariñas City, Cavite - the southern province of Luzon island and is 42 kilometers south of Manila. Barangay Salawag, situated in the northeastern part of Dasmariñas City, was named as such because of the presence of the bamboo trees; or in Tagalog, salawag. It is the largest barangay of the city in terms of land area and population (80,000). However, despite the huge population and many subdivisions and schools, no public library can be found.